New Hybrid Polyurea-Polyurethane Elastomers with Antistatic Properties and an Influence of Various Additives on Their Physicochemical Properties - Szymon Kosiński; Marcin Gonsior; Piotr Krzyżanowski; Iwona Rykowska (Molecules, 2021)
Polyurea is a synthetic high-strength elastomeric material that can be sprayed as a coating over existing structures in order to protect against weathering effects. It is ideal for anti-corrosion protection and is characterized by excellent mechanical properties and adhesion to various surfaces. Further development of this technology may allow obtaining new coatings with improved antistatic properties, which would be an excellent alternative compared to used antistatic epoxy paints. This paper will examine the influence of tetraalkylammonium salt (1), potassium hexafluorophosphate solution (2) and imidazolium-based ionic liquid (3) on the improvement of antistatic properties of the polyurea-polyurethane coatings. In addition, the modified samples were also verified in terms of changes in mechanical properties and the appearance of functional groups other than in the reference sample, as well as surface defects that may arise due to incompatibility of the antistatic additive with the polymer matrix. In order to obtain information about the properties mentioned above, the electrical resistance was determined, the tensile strength and elongation were measured, FT-IR spectra were made, and images were taken with the use of scanning electron microscopy. The conducted research showed that the antistatic properties of the tested hybrid coatings could be improved, but their use may be associated with certain limitations that should be taken into account when designing such materials.